Effects of mono- and dual-frequency ultrasounds on structure and physicochemical properties of faba bean proteins - Shuyang Wang; Song Miao; Mohammad Hassan Kamani; Eoin G. Murphy; Da-Wen Sun (Ultrasonics Sonochemistry)
Faba bean proteins are currently viewed as promising animal protein alternatives. However, certain functional properties e.g. relatively low solubility compared to whey protein isolates, can limit the application of faba bean protein isolates (FPIs) in certain food products. Therefore, it may be desirable to use modification approaches such as the application of ultrasound to alter such limiting physicochemical properties. In this study, Faba Bean Protein Isolates (FPIs) were treated by ultrasound with different frequencies (20 kHz, 40 kHz and 20 + 40 kHz) prior to hydration (1 %) at different pH levels (3, 7, and 9). Then the structure and physicochemical properties (i.e. particle size, ζ-potential, surface hydrophobicity, thermal behavior, and solubility) of control and untreated FPIs were investigated. Ultrasound treatment had no obvious effect on the molecular weight of FPIs, whereas it changed the secondary structure of FPIs from a more ordered structure to a more disordered structure. The applied treatment resulted in an increase in surface hydrophobicity across all treatment levels and pHs. It also decreased the particle size of FPI at pH 3, while it increased the particle size at pH 7 and 9, compared to the untreated FPI. In addition, the solubility and thermal properties of FPI were modified through the ultrasound treatment. The higher solubility of FPI could improve its potential to be used as a functional ingredient for many food applications. Ultrasound treatment at 20 kHz and 20 + 40 kHz had more effects on the physiochemical properties of FPI compared to that at 40 kHz. Overall, ultrasound treatment with different frequencies (20 kHz, 40 kHz, and 20 + 40 kHz) modified the structure and physiochemical properties of FPI to different degrees and may be beneficial for the development of FPI for certain food applications.